A DNA-Schiff base functional nanopore sensing platform for the highly sensitive detection of Al3+ and Zn2+ ions. Issue 6 (20th January 2023) - Zhou, Shuailong; Ye, Jianhan; Zhao, Xiaohuan; Zhou, Zihao; Dong, Yuanchen; Shi, Qian; Liu, Nannan; Wu, Fen
Abstract : The DNA-Schiff base functional nanopore sensing platform has been developed for highly sensitive detection of Al 3+ and Zn 2+ ions. Abstract : The combination of DNA nanotechnology and nanopore sensing technology has greatly promoted research on target molecule or ion detection. The large solid-state nanopores/nanochannels show better mechanical stability and reproducibility, but metal ion detection in the large nanopores with diameters of hundreds of nanometers or several micrometers is rarely reported. Hence, it is meaningful and urgent to develop a large nanopore-based sensing platform for the detection of metal ions. Herein, we employed a salicylic aldehyde-modified DNA network in conjunction with a glass nanopipette (GN) with a diameter of hundreds of nanometers as a sensing platform for the detection of target metal ions. Upon the addition of different receptors with the amino group, the salicylic aldehyde could in situ specifically recognize and bind with Zn 2+ and Al 3, forming Schiff base-metal ion complexes at the four vertices of one face per nanocube unit. The steric hindrance effect of multiple Schiff bases and metal ion complexes leads to the blockage of internal structure and decrease of ion current in the GN. Owing to this signal amplification strategy, the detection limit of the target metal ion reaches a level of fM in the GN with a diameter of about 300 nm. In the future, this functional nanopore sensing platform is expected to realize highly sensitive detection for more biological metal ions by choosing appropriate receptors.